Senegal : Poverty Reduction Strategy Paper-Annual Progress Report-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2005)
This paper presents the Joint Staff Advisory Note on Senegal's Poverty Reduction Strategy Paper Annual Progress Report. Senegal's poverty reduction strategy is built on four pillars that include wealth creation, capacity building, the provision of basic social services, and improving the living conditions of vulnerable groups. In spite of the economic slowdown caused by poor weather conditions in 2002, the government continued to focus on enhancing revenue mobilization, prudent public expenditures execution, and reallocation of public resources to social sectors.